Perhitungan Arah Kiblat dan Keterkaitannya dengan Akurasi Ibadah dan Literasi Masyarakat - Rahma Awalia; Chintya; Dupit Malinda (Jurnal Pelita Nusantara, 2025)
Determining the Qibla direction is a fundamental discourse at the intersection of Islamic astronomy (Ilmu Falak) and Islamic jurisprudence (Fiqh), bearing direct implications for the validity of Muslim worship. This research report provides an in-depth examination of the urgency of Qibla direction accuracy in resolving everyday problems, focusing on a socio-religious case study in Sambas Regency, West Kalimantan Province. The Sambas Malay-Muslim community is known for its deeply rooted religious traditions; however, sociological dynamics frequently give rise to debates and cognitive conflicts concerning the shifting of the Qibla direction, affecting both the spatial layout of mosques and the orientation of burials (liang lahad). Employing a mixed-methods approach that integrates quantitative calculations based on spherical trigonometry with qualitative observations of the community's socio-cultural practices, this research formulates precise Qibla direction coordinates for the Sambas region. Mathematical calculations indicate that the average Qibla azimuth for the center of Sambas Regency is at an angle of 292°28’55’’ from True North towards the East-South-West, or extending 67°31’05" from North to the West. The conclusion of this extensive study asserts that integrating the mathematical certainty of Islamic astronomy with a sociological wisdom approach is highly crucial in implementing Qibla direction corrections to prevent horizontal conflicts within the traditional Sambas community.